Structural insights into RapZ-mediated regulation of bacterial amino-sugar metabolism. Issue 18 (5th September 2017) - Gonzalez, Grecia M.; Durica-Mitic, Svetlana; Hardwick, Steven W.; Moncrieffe, Martin C.; Resch, Marcus; Neumann, Piotr; Ficner, Ralf; Görke, Boris; Luisi, Ben F.
Abstract: In phylogenetically diverse bacteria, the conserved protein RapZ plays a central role in RNA-mediated regulation of amino-sugar metabolism. RapZ contributes to the control of glucosamine phosphate biogenesis by selectively presenting the regulatory small RNA GlmZ to the essential ribonuclease RNase E for inactivation. Here, we report the crystal structures of full length Escherichia coli RapZ at 3.40 Å and 3.25 Å, and its isolated C-terminal domain at 1.17 Å resolution. The structural data confirm that the N-terminal domain of RapZ possesses a kinase fold, whereas the C-terminal domain bears closest homology to a subdomain of 6-phosphofructokinase, an important enzyme in the glycolytic pathway. RapZ self-associates into a domain swapped dimer of dimers, and in vivo data support the importance of quaternary structure in RNA-mediated regulation of target gene expression. Based on biochemical, structural and genetic data, we suggest a mechanism for binding and presentation by RapZ of GlmZ and the closely related decoy sRNA, GlmY. We discuss a scenario for the molecular evolution of RapZ through re-purpose of enzyme components from central metabolism.